Pengamanan Citra Digital Berbasis Kriptografi Menggunakan Algoritma Vigenere Cipher - Imam Riadi; Abdul Fadlil; Fahmi Auliya Tsani (UIN Sunan Kalijaga Yogyakarta, 2022)
Cryptography is one of the most popular methods in data security by making data very difficult to read or even unreadable. One of the well-known techniques or algorithms in cryptography is Vigenere Cipher. This classic algorithm is classified as a polyalphabetic substitution cipher-based algorithm. Therefore, this algorithm tends to only handle data in text form. By this research, a console-based application has been developed which is made from PHP programming language to be able to encrypt and decrypt digital image media using Vigenere Cipher. The encryption process is done by first converting a digital image into a base64 encoding format so that the encryption process can be carried out using the tabula recta containing the radix-64 letter arrangement used for base64 encoding. Conversely, the decryption process is carried out by restoring the encrypted file using radix-64 letters, so we get the image file in the base64 encoding format. Then, the image with the base64 encoding format is decoded into the original file. The encryption process took less than 0,2 seconds and 0.19 seconds for the decryption process and 33.34% for average file size addition on the encrypted file from the original file size. Testing on ten different images with different sizes and dimensions showed a 100% success rate which means this research was successfully carried out.